Finite element modeling of hot rolling of 1075 carbon steel process with variable cross section. - Montemayor de la Garza, Karina; Zambrano Robledo, Patricia del Carmen; Zapata Hernández, Óscar Jesús; Leduc Lezama, Luis Adolfo (2022)
Currently, it is common to use steel poles for applications in livestock and agriculture. In this work, finite element analysis of five hot rolling passes for the manufacture of farm poles using 1075 carbon steels from recycled railway material was developed. The steel industry in Mexico imports products from other countries or from companies specialized in metallurgy at an excessive cost. To be more competitive and save costs, companies seek the reutilization of existing resources such as the railway 1075 steel, which has good mechanical properties. SFTC DEFORM‑3D software was used to model five hot rolling passes considering a variable cross section railway profile. The effect of rolling speed and temperature were considered to analyze flow behavior. Rolling loads were also determined.